Liberdade e justiça em John Rawls e Robert Nozick - Müller, Rafael (My University, 2020)
This dissertation has as its theme the relationship between the concepts of freedom and justice developed by John Rawls (Justice as Fairness) and Robert Nozick (Libertarianism). Both authors talk about similar subjects and take equivalent starting points, but the weight given to the plurality of worldviews between individuals in a society differs notably between Rawls and Nozick, leading to different conclusions. In the carried-out analysis, I sought to identify the points of congruence and divergence in the conceptual relationships between the authors. I assessed in both theoretical propositions the extent to which (and to what extent) individuals, whether they are citizens or political institutions, can interfere through their actions in each other's freedoms and how just these interferences are. At the end of the dissertation, I sought to find the ideal balance between freedom and justice in a society, pointing out that the greater the morality of its people, the smaller the State can be and, consequently, its interference in the lives of individuals.
Esta dissertação tem como tema as particularidades da relação entre os conceitos de liberdade e justiça desenvolvidos por John Rawls (Justiça por Equidade) e Robert Nozick (Libertarianismo). Ambos autores discorrem sobre assuntos similares e tomam pontos de partida parecidos, mas o peso dado para a pluralidade de visões de mundo entre indivíduos em uma sociedade difere notavelmente entre Rawls e Nozick, levando-os conclusões diferentes. Na análise realizada, busquei identificar quais os pontos de congruência e divergência nas relações conceituais entre os autores. Avaliei em ambas proposições teóricas a partir de que ponto (e até que ponto) os indivíduos, sejam eles cidadãos ou instituições políticas, podem interferir através de suas ações nas liberdades uns dos outros e o quão justas são estas interferências. No final da dissertação, busquei encontrar qual o ideal equilíbrio entre liberdade e justiça na sociedade, apontando que quanto maior a moralidade de um povo, menor poderá ser o tamanho do Estado e, por consequência, as interferências deste na vida dos indivíduos.
Keywords: Rawls, John, 1921-2002; Nozick, Robert, 1938-2002; Liberalismo; Liberdade; Justiça; Liberalism; Liberty; Justice